Dermatoglyphics and Type 2 Diabetes Mellitus: Review - Falah S. Al-Fartusie (Journal of Global Pharma Technology, 2016)
Study of epidermal ridges on the skin covers the palmar and plantar surface of hands and soles, and is known as Dermatoglyphics (also known as fingerprints). Dermatoglyphics patterns are genetically determined and are affected by environmental factors in the uterus. After their formation, they remain stable, unchanged, and are not affected by postnatal environment or age. Dermatoglyphics can serve as a reliable marker of individual identification, as they can be a morphological trait, and a mirror to explain genetic and environmental factors in the first trimester of pregnancy. Diabetes is a chronic disease with serious complications if not managed well. In fact, 90% of diabetics are type 2 diabetes mellitus, multifactorial metabolic syndrome. T2DM will not be diagnosed until the long-term complications. Early diagnosis and treatment are very important to prevent long-term complications of the disease (such as retinopathy, neuropathy, nephropathy), and predicting people with high risk of T2DM can be useful in preventing disease and complications. In this review, we will discuss dermatoglyphics, and the main results of researchers who studied Dermatoglyphics for T2DM patients.Keywords: Dermatoglyphics, T2DM, Arch, Loop, Whorl, Ridge count.